Elimination of the transmission mother-to-child HIV and syphilis: the progress and challenges to Ukraine - Derevyanko, Lyudmyla; Martsynovska, Violeta (ScienceRise: Medical Science, 2017)
The objective of this study is to analyze the indicators of impact and process of EMTCT of HIV and syphilis in Ukraine thus helping to prepare for validation of this process according to the WHO targets and сriteria. Materials and Methods. In this retrospective study were presented the epidemiological and clinical data about 237 women who had syphilis before or during pregnancy and babies born to them (238) from 1999 to 2007 yy. Besides in article were used statistical forms of the Public Health Center and Center for Medical Statistics of the Ministry of Health of Ukraine for the incidence of syphilis and HIV in women of reproductive age, pregnant women and children born to them, including those who were diagnosed with congenital syphilis and HIV infection from 2007 to 2016 yy Results. The analysis of the data from Public Health Center shows that one of the target indicators for the impact of HIV/AIDS has been achieved in Ukraine: the number of new cases of mother-to-child transmission of HIV per 100,000 live births was 20.8 in 2015. But in the same time the indicator of mother-to-child transmission of HIV in Ukraine is still higher than the WHO minimum criterion (≤2%) and was 3.7% according to a cohort of children born to HIV-infected women in 2015, which still does not meet the criteria WHO to validate this process. Despite the main target indicator of CS elimination has been achieved, some process indicators of syphilis as coverage of syphilis testing and treatment of pregnant women have not reached yet. Conclusions. Given the policy of dual elimination of MTCT of HIV and syphilis in Ukraine, an expansion of the PMTCT program on universal access to HIV and syphilis diagnostics and treatment services in pregnant women at high-risk groups is reguired.